Concepts, models and measurement of continuity of care in mental health services: A systematic appraisal of the literature - Michael Coffey (Journal of Psychiatric and Mental Health Nursing, 2017)
The increased complexity of community mental health services, and associated fragmentation of traditional dividing lines between services, has underscored the centrality of care continuity and coordination in modern mental healthcare. However, clarification of the key features of the care continuity concept has proved difficult and a consensus has not been reached. This review draws together and critically examines latest evidence concerning concepts, models and scales based on a multi-dimensional understanding of care continuity.Databases ASSIA, Pubmed, Medline and Cochrane were searched for papers dating from January 2005 to July 2016, of which 21 articles met inclusion criteria. These were subjected to quality appraisal based on CASP and COSMIN checklists. Studies were grouped into three thematic categories describing concepts, models and scales of care continuity. Synthesis indicated correspondence between independent, multi-dimensional models of care continuity, providing greater clarity regarding the essential features of the concept. Association, though not causation, between care continuity factors and health outcomes is supported by current evidence. Clarification of care continuity in mental health services may enable nurses working as care coordinators to develop a better understanding of key elements of their role, and provide guidance for future service development.